2018
DOI: 10.1038/s41598-018-27549-0
|View full text |Cite
|
Sign up to set email alerts
|

Unexplored photoluminescence from bulk and mechanically exfoliated few layers of Bi2Te3

Abstract: We report the exotic photoluminescence (PL) behaviour of 3D topological insulator Bi2Te3 single crystals grown by customized self-flux method and mechanically exfoliated few layers (18 ± 2 nm)/thin flakes obtained by standard scotch tape method from as grown Bi2Te3 crystals. The experimental PL studies on bulk single crystal and mechanically exfoliated few layers of Bi2Te3 evidenced a broad red emission in the visible region from 600–690 nm upon 375 nm excitation wavelength corresponding to optical band gap of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…2f). Broadband absorption from 260 nm to 1500 nm, is observed for Bi 2 Te 3 NPs-1 and Bi 2 Te 3 NPs-2, which is in good agreement with previously reported results, 40,41 implying great potential for application in broadband optoelectronic devices. Besides, Tauc plots of Bi 2 Te 3 NPs-1 and Bi 2 Te 3 NPs-2 ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…2f). Broadband absorption from 260 nm to 1500 nm, is observed for Bi 2 Te 3 NPs-1 and Bi 2 Te 3 NPs-2, which is in good agreement with previously reported results, 40,41 implying great potential for application in broadband optoelectronic devices. Besides, Tauc plots of Bi 2 Te 3 NPs-1 and Bi 2 Te 3 NPs-2 ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, under the near-infrared light illumination, it indeed has an obvious thermal effect, especially at higher incident light intensities, so we cannot completely rule out the existence of thermoelectric currents. However, by reviewing the related literatures [41,42], we found that the maximum thermoelectric currents are usually below a few microamperes, while the measured photocurrent in this work at a similar incident light intensity is usually 3-5 orders of magnitude higher than the thermoelectric current. Importantly, the response speed of the thermoelectric current is usually above the order of a few seconds, while the response speed of this device is about 5-6 orders of magnitude faster than the thermoelectric current.…”
Section: Resultsmentioning
confidence: 55%
“…Importantly, a remarkable current switching characteristic was observed under the 1064 nm light irradiation, even under the applied zero bias voltage. This performance indicates that the photonic emission and spontaneously interfacial charge transfer can contribute to the significant photocurrent output of the device [41,42]. Furthermore, the current switching ratio can be regulated by the intensity of incident lights, as shown in figure 3(b).…”
Section: Resultsmentioning
confidence: 86%
“…TIs are insulating materials in the bulk, while presenting metallic conducting surface states, which are topologically protected with spin polarization locked to crystal momentum [5]. The unique electronic and optical properties associated with these surface states make them strong candidates to study innovative quantum phenomena and to explore practical applications for quantum computing, spintronics and nano technological devices [11,12]. Since the most interesting properties of the TIs are related to their surface, the first step for exploiting the unique properties of Bi2Te3 is to have homogeneous, wafer-scale, large-domain size and defect-free layer growth, with a high surface-to-bulk ratio [8,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…TIs are insulating materials in the bulk, while presenting metallic conducting surface states, which are topologically protected with spin polarization locked to crystal momentum . The unique electronic and optical properties associated with these surface states make them strong candidates to study innovative quantum phenomena and to explore practical applications for quantum computing, spintronics, and nanotechnological devices. , It has been shown that chalcogenide materials like Bi 2 Te 3 , Sb 2 Te 3 , Bi 2 Se 3 , or Ge–Sb–Te are linked by the metavalent bonding mechanism , identified as the source of their remarkable properties. Moreover, for group-IV monochalcogenide monolayers, further possibilities are offered when considering the corresponding two-dimensional (2D) materials, extending them to valleytronic and optoelectronic applications .…”
Section: Introductionmentioning
confidence: 99%